Envisioning collective action for sustainable resource management. An economic experiment - Juan Felipe Ortiz-Riomalo; Stefanie Engel; Ann-Kathrin Koessler (ZBW – Leibniz Information Centre for Economics, 2024)
Participatory vision-building (PVB) seems promising in fostering collective action to overcome complex social-environmental dilemmas and to attain socially desirable outcomes. By assisting the relevant actors in visualising their desired future and imagining how it would feel to be an active part of it, PVB makes the stated goals experiential, inspirational and meaningful, galvanising collective action. Nevertheless, it is still unclear whether PVB's causal impacts on collective action go beyond those of other elements of participatory processes that PVB also comprises, i.e. social interaction, information exchange and coordination around desirable strategies, outcomes or futures. We contribute to filling this gap through a (pre-registered) framed lab-in-the-field economic experiment conducted with 728 farmers from Lake Tota, Colombia. Participants chose between two stylised farming practices over multiple hypothetical growing seasons, impacting their seasonal earnings and the water levels of a hypothetical lake as a shared resource. We compare the behaviour of participants in a PVB treatment, in which they discussed and imagined a desired vision for the future, against the behaviour of participants in three control conditions. Albeit potentially effective for cooperation, the effects of PVB were found to be statistically indistinguishable from other participatory processes with similar aims. However, exploratory analysis suggests there might be potential impacts of PVB on emotions and preferences for pro-environmental and pro-social action. Future research could test the generalisability of our findings to other contexts, particularly those with heterogeneous interests, delve deeper into the underlying psychological mechanisms, and explore the interplay with other institutional mechanisms for fostering sustained collective action.
Is replaced by the following version: https://hdl.handle.net/10419/323849
Keywords: D02; D70; D91; H40; Q20; Q24; Q25; Q57; Q59; 330; collective action; social dilemmas; natural resource management; participatory processes; participatory governance; visioning